2009
DOI: 10.1099/jmm.0.002907-0
|View full text |Cite
|
Sign up to set email alerts
|

Membrane transporter proteins are involved in Trichophyton rubrum pathogenesis

Abstract: Trichophyton rubrum is a dermatophyte responsible for the majority of human superficial mycoses. The functional expression of proteins important for the initial step and the maintenance of the infection process were identified previously in T. rubrum by subtraction suppression hybridization after growth in the presence of keratin. In this study, sequences similar to genes encoding the multidrug-resistance ATP-binding cassette (ABC) transporter, copper ATPase, the major facilitator superfamily and a permease we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 39 publications
0
35
0
1
Order By: Relevance
“…The resistance of dermatophytes to inhibiting agents involves the participation of target-enzyme modifiers and overexpression of ATP-binding cassette (ABC) transporters and stress-related proteins (23). In T. rubrum, two ABC transporters, TruMDR1 and TruMDR2, were identified as responsible for resistance to various antifungal drugs, such as ITC and TRB (24,25). Candida albicans clinical isolates resistant to azole compounds and overexpressing the ABC transporter gene products CDR1 and CDR2 are less susceptible to the morpholine derivative AMF (26).…”
Section: Discussionmentioning
confidence: 99%
“…The resistance of dermatophytes to inhibiting agents involves the participation of target-enzyme modifiers and overexpression of ATP-binding cassette (ABC) transporters and stress-related proteins (23). In T. rubrum, two ABC transporters, TruMDR1 and TruMDR2, were identified as responsible for resistance to various antifungal drugs, such as ITC and TRB (24,25). Candida albicans clinical isolates resistant to azole compounds and overexpressing the ABC transporter gene products CDR1 and CDR2 are less susceptible to the morpholine derivative AMF (26).…”
Section: Discussionmentioning
confidence: 99%
“…T. rubrum secretes many proteolytic enzyme-like metallocarboxypeptidase, serine carboxipeptidase with a glycosylphosphatidilinositol anchor that may contribute to fungal virulence [34,35], and hemolysins in T. verrucosum infection. [3] Dermatophytes evade host immune system by several mechanisms: (1) cell wall glycoproteins, endoproteases, and exoproteases isolated from T. rubrum and M. canis; (2) producing the lysine motive binding domain by securing fragments of chitin or even producing mannans associated with glycoprotein; (3) provoking the release of anti-inflammatory cytokines and TLR blockade (mainly TLR2), and therefore leading to (4) generation of T regulatory cells with strong immunosuppressive potential; and thus (5) the blockade of Th1 response (by suppressing the activity of keratinocytes and dendritic cells), and activating Th2 response which is unable to control fungal infection, leading to chronic inflammation as seen in MG [36,37,38…”
Section: Fungal Pathogenesismentioning
confidence: 99%
“…ATP-binding cassette (ABC) transporters are involved in a variety of processes such as nutrient uptake, pathogenesis, and efflux pumping of structurally unrelated drugs with different modes of action (Jones et al, 2014;Maranhão et al, 2009). They act effectively in drug efflux, decreasing the accumulation of cytotoxic agents in the intracellular milieu, thus playing a significant role in multidrug resistance (MDR) mechanisms (Higgins, 1992;Wirsching et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic analysis of the T. interdigitale mdr2 knockout (Dmdr2) strain showed that MDR2 modulates the susceptibility to terbinafine (Fachin et al, 2006). Furthermore, high transcription levels of the mdr2 gene in T. interdigitale during mimetic infection (Maranhão et al, 2007), and reduced virulence in Dmdr2 mutants in an ex vivo infection model, suggest that this transporter is also involved in fungal pathogenicity (Maranhão et al, 2009). In Candida albicans, loss-of-function or inhibition of one ABC transporter activates different transporters, resulting in compensatory effects that modulate the efflux of antifungal drugs (Sanglard et al, 1997).…”
Section: Introductionmentioning
confidence: 99%